Bilateral agreement for the period 2011/2013 LLP/Erasmus Programme: higher education - Erasmus between Universidade Lusíada de Lisboa and Universidad Católica San Antonio de Murcia - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme; - Subject area: Architecture; Law; Economics; Sport; Psychology.